Відмовостійкий алгоритм ідентифікації бортової математичної моделі авіаційного двигуна ТВ3-117 в складі його системи автоматичного управління - Владов, С. І.; Vladov, S. I.; Ковальський, В. С.; Kovalskyi, V. S.; Дятловська, В. Л.; Diatlovska, V. L.; Яніцький, А. А.; Yanitskyi, A. A.; Вакуленко, Р. А.; Vakulenko, R. A.; Serhii Vladov (Вісник Херсонського національного технічного університету. - 2020. - № 4(75). - С. 11-19, 2020)
Розроблено відмовостійкі алгоритми ідентифікації бортової математичної моделі авіаційного двигуна ТВ3-117 в складі його системи автоматичного управління в польотних режимах. Обґрунтувано доцільність використання Калман-фільтрації в системі автоматичного управління авіаційного двигуна ТВ3-117, визначено передавальна функція фільтра Калмана, алгоритм виявлення та локалізації відмови каналу двоканального датчика. Досліджено частотні властивості системи автоматичного управління авіаційного двигуна ТВ3-117, підтверджено і доведено рівність одиниці коефіцієнта посилення розробленого відмовостійкого блоку фільтрації і відсутності додаткових фазових зсувів, внесених можливим чистим запізненням, обумовленим особливостями реалізованих алгоритмів виявлення відмов вимірювальних каналів і Калман-фільтрації вхідної інформації бортової вбудованої математичної моделі.

The subject matter of the article is TV3-117 aircraft engine and methods for monitoring and diagnosing its technical condition. The goal of the work is development of fault-tolerant algorithms for identification of the onboard mathematical model of the TV3-117 aircraft engine as part of its automatic control system in flight modes. The following tasks were solved in the article: recovering of lost information by an auto-associative neural network in case of a single sensor failure, recovering of lost information by an «optimal» autoassociative neural network in case of single sensor failures of the on-board control and diagnostic system, recovering of lost information by an auto-associative neural network and an on-board control and diagnostic system from the gas temperature registration sensor in front of the turbine compressor in case of failure. The following methods used are – substantiation of expediency of Kalman-filtration use in TV3-117 aircraft engine automatic control system, determination of Kalman filter transfer function, determination of algorithm of detection and localization of channel failure of two-channel sensor, determination of frequency characteristics of TV3-117 aircraft engine automatic control system, proof of equality of unit coefficient fault-tolerant filter unit. Conclusions: The frequency properties of the automatic control system of the aircraft engine TV3-117 are investigated, the equality of the unit of the gain of the developed fault-tolerant filtering unit and the absence of additional phase shifts introduced by the possible net delay due to the peculiarities of the implemented algorithms mathematical model. The absence of their influence on the stability of aircraft engine TV3-117 automatic control system is proved. Approbation of the developed algorithms showed that the average relative error in dynamics does not exceed 0.15 %, and in statics at the maximum expense – decreases to 0.01 % that corresponds to modern requirements of accuracy of algorithms of identification on a contour of dosing needle.

Разработан отказоустойчивый алгоритм идентификации бортовой математической модели авиационного двигателя ТВ3-117 в составе его системы автоматического управления в полетных режимах. Исследованы частотные характеристики системы автоматического управления авиационного двигателя ТВ3-117, подтверждено и доказано равенство единице коэффициента усиления разработанного отказоустойчивого блока фильтрации и отсутствие дополнительных фазовых сдвигов, вносимых возможным чистым опозданием, обусловленным особенностями реализованных алгоритмов обнаружения отказов измерительных каналов и Калман-фильтрации входящей информации бортовой встроенной математической модели.
Failure-tolerant identification algorithm of the on-board mathematical model of TV3-117 aircraft engine as a part of its automatic control system
Отказоустойчивый алгоритм идентификации бортовой математической модели авиационного двигателя ТВ3-117 в составе его системы автоматического управления
Keywords: Техніка. Технічні науки. Machinery. Engineering. Техника. Технические науки; Наукові публікації. Scientific publications. Научные публикации; авіаційний двигун ТВ3-117; aircraft engine TV3-117; авиационный двигатель ТВ3-117; Калман-фільтрація; Kalman filtering; Калман-фильтрация; система автоматичного управління; automatic control system; система автоматического управления; локалізація відмови; failure localization; локализация отказа; відмовостійкий алгоритм; fault-tolerant algorithm; отказоустойчивый алгоритм